Cattle-related trauma: a 10-year retrospective cohort study of patients admitted to a single tertiary trauma centre in Switzerland (Swiss Medical Weekly, 2022)
AIMS OF THE STUDY: Switzerland is traditionally an agricultural country with more than 50,000 farms and 1.5 million registered cows. However, contemporary literature on cattle-related trauma in Switzerland remain limited. The purpose of this study was to examine injury patterns and outcomes of patients who presented to a tertiary trauma centre in Switzerland following cattle-related trauma.METHODS: Retrospective single-centre study over a 10-year period (2012–2021) including all patients experiencing cattle-related trauma. From retrieved charts demographics, injury data, and outcomes were collected and subsequently analysed.RESULTS: A total of 94 patients with cattle-related injuries were identified. The median age was 52 years (interquartile range [IQR] 37–63) and 75% were male. Cattle-related injuries were most frequent among farmers (73%) and were most often caused by cows (86%), followed by bulls (10%). Blunt trauma (89%) was the leading mechanism of injury including headbutt (36%), kick (35%), physical contact (20%) and trampling injury (12%). Penetrating injury occurred in 11%, all caused by headbutt. Contusions (82%) and lacerations (45%) were the leading injuries, followed by face fractures (28%), closed head trauma (19%) and chest injuries (17%). Overall, 10% of all patients had a head abbreviated injury scale (AIS) score of ≥3 and 8% had a chest AIS of ≥3. The hospital admission rate was 49% for cow-related injury vs 90% for bull-related injuries, p = 0.023. Overall, in-hospital mortality was 3% and the median length of stay was 4.5 days (IQR 3–8) among patients admitted to the hospital.CONCLUSIONS: Cattle-related injuries in Switzerland mainly affect farmers and are associated with considerable morbidity, especially when caused by bulls. Facial fractures, head injuries and chest injuries are common, and the latter two in particular can be severe. The results of the present study can be used for the implementation of data-driven prevention measures for the safe handling of cattle in Switzerland.